1987
DOI: 10.1002/clc.4960100302
|View full text |Cite
|
Sign up to set email alerts
|

Position as a variable for cardiovascular responses during exercise

Abstract: Summary: Twenty-one normal young male subjects underwent resting and exercise (bicycle) radionuclide angiography in the full supine and 70" upright tilt positions in order to examine the effects of position on left ventricular size and performance, hemodynamics, and exercise duration. All subjects also underwent full (90") upright bicycle ergometry with respiratory gas analysis to establish the level of maximal exercise capacity for each. Body position significantly (p < 0.05) affected resting and exercise car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…In the current study, at the work load = 50 watts, both heart rate and SVi increased with heart rate being the greater contributor to increased blood flow and stroke index more variable. These results are consistent with others reporting supine exercise in the catheterization laboratory (dye) and with other imaging modalities used in current practice to dynamically assess cardiac function .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, at the work load = 50 watts, both heart rate and SVi increased with heart rate being the greater contributor to increased blood flow and stroke index more variable. These results are consistent with others reporting supine exercise in the catheterization laboratory (dye) and with other imaging modalities used in current practice to dynamically assess cardiac function .…”
Section: Discussionsupporting
confidence: 91%
“…In health, it is known that exercise capacity is influenced by subject age, gender, level of conditioning, hydration status, and environmental factors . The assessment of an individual's exercise capacity is also influenced by body position and exercise protocol . Although maximal aerobic capacity was not reported at the time of cardiac catheterization in our active duty soldiers, the variability in resting heart rate within the study population suggest that levels of aerobic conditioning varied and with a portion of the subjects (resting HR < 60 bpm) likely well‐conditioned at the time procedures were performed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In general, the AT and peak VO2, which are determined from cardiopulmonary exercise testing, were lower in the supine position than in the upright position 5)8) . Left ventricular end diastolic pressure (LVEDP) and SV in the supine position were higher than those in the upright position at rest and during moderate exercise 12) . The difference in LVEDP and SV are gradually reduced as the work intensity increases 13) .…”
Section: Discussionmentioning
confidence: 92%
“…The CO and SV at the backrest angle of 60° was especially significantly greater, as compared with that at the 20° backrest angle. Cotsamire 12) and Thadani 13) reported that the CO and left ventricular end diastolic volume in supine exercise showed a significantly higher value than that in sitting exercise. Rowell 14) reported that the blood flow volume in the lung and the abdominal cavity increases more in the horizontal position than in the vertical position.…”
Section: Discussionmentioning
confidence: 96%